Intrauterine fetal growth restriction in sheep leads to sexually dimorphic programming of Preadipocytes' differentiation potential - Michell Goyal; Rosa I. Luna Ramirez; Sean W. Limesand; Ravi Goyal (Physiological Reports)
Abstract Fetal growth restriction (FGR) is a risk factor for obesity in adult life. Importantly, growth‐restricted females are more prone to obesity than males. The mechanisms involved in this sexually dimorphic programming are not known. Previously, we have demonstrated that ambient hyperthermia (40°C) led to placental insufficiency and significant FGR, and the perirenal adipose tissue undergoes sexually dimorphic gene expression. We demonstrated that males undergo significant changes in gene expression with growth restriction. This was not the case in females. We have also demonstrated that the isolated preadipocytes from male FGR (MFGR) have reduced differentiation potential compared to control males & females and female FGR (FFGR). Thus, we hypothesized that growth restriction differentially programs gene expression and genetic pathways in perirenal preadipocytes, which reduces their differentiation potential in male fetuses in a sexually dimorphic manner. We created FGR by exposing pregnant sheep to ambient hyperthermia. After isolating preadipocytes from perirenal adipose tissue, we differentiated them following published protocols. We examined the gene expression before and after differentiation from control male, control female, MFGR, and FFGR female. We also compared our data with other published studies in mouse and human preadipocytes. Our results demonstrate that a set of 21 genes altered with preadipocyte differentiation to mature adipocytes is common in adipose tissue from both sexes, humans, mice, and sheep, at different organismal ages (embryonic, fetal, and adult) and different sites (subcutaneous inguinal, pancreatic, perirenal). We also demonstrate that female FFGR fetuses demonstrate all these 21 genes altered similar to control males and females; however, MFGR fetuses have six genes (Dgat2, Fabp4, Lipe, Lrrfip1, Spred3, and Thrsp) that are not changed with preadipocyte differentiation to mature adipocyte. These genes may be responsible for reduced differentiation potential and obesity in FGR males compared to FGR females. Another important finding of the present study is that Lrrfip1, known to be associated with obesity, was upregulated with FGR and requires further investigation. Overall, our studies provide several target genes that may play a crucial role in reducing the risk of MFGR for obesity.